Herbal Medicines for Irinotecan-Induced Diarrhea - Tang, Liu; Li, Xiaolei; Wan, Liping; Xiao, Yao; Zeng, Xin; Ding, Hong (Frontiers in Pharmacology, 2019)
Irinotecan (CPT-11), a water-soluble derivative of camptothecin, belongs to the class of DNA topoisomerase I inhibitors and has been approved worldwide for the treatment of advanced colorectal cancer, lung cancer, and malignant lymphoma. Although CPT-11-based chemotherapy is widely used, severe gastrointestinal (GI) toxicity, especially late-onset diarrhea, is a common adverse reaction, limiting clinical application of the drug. The incidence of grade 3 or 4 diarrhea is high, with 20%–40% of CPT-11-treated patients experiencing this adverse effect. High-dose loperamide and octreotide are generally recommended for treatment of CPT-11-induced diarrhea. However, in clinical practice, loperamide is associated with a significant failure rate and the beneficial effects of octreotide are controversial. An accumulating number of recent studies have suggested that medicinal herbs and their derived phytocompounds may be effective complementary treatments for CPT-11-induced diarrhea. In this mini-review, we briefly summarize currently available literatures regarding the formulae and herbs/natural products used as adjuvants in animal and clinical studies for the treatment of diarrhea caused by CPT-11.